Methods for evaluating the quality of edge detectors operation in MATHCAD software package - Bilynskyi, Yosyp; Knysh, Bogdan; Kulik, Yaroslav (Scientific Works of Vinnytsia National Technical University, 2017)
A technique is developed for evaluating the quality of edge detector operation in Mathcad package, which makes it possible to estimate effectiveness of edge detectors in their work with various types of images and to use the obtained research results for elaboration of scientific and educational materials for image processing-related disciplines.